Stem cell therapy for glaucoma—there is still a long way to go - Li, Fei; Zhang, Xiulan (Annals of Eye Science, 2017)
Glaucoma is now the second leading reason of blindness in the world and is characterized by gradual loss of retinal ganglion cells. Stem cells have the ability to regenerate human structures. Although there are still problems unsolved, stem cell therapy might provide brighter future for treatment of glaucoma.